Obstetric and neonatal outcomes in the management of twin pregnancies with gestational diabetes using the IADPSG criteria for singleton pregnancies - Jue Ma; Dongjian Yang; Juanxiu Lv; Shujing Liu; Li Gao; Yan Bi; Yanlin Wang (BMC, 2024)
Abstract Background This study evaluates the effectiveness of the International Association of Diabetes and Pregnancy Study Groups (IADPSG) criteria, typically applied to singleton pregnancies, in managing gestational diabetes mellitus (GDM) in twin pregnancies. Focusing on a Chinese cohort, it contrasts the clinical outcomes and complications in twin pregnancies with and without GDM. Methods We conducted a retrospective cohort study at our hospital from January 2019 to December 2021, including all twin deliveries except those before 28 weeks of gestation, with prior diabetes, or unknown GDM status. GDM was diagnosed using a 75 g oral glucose tolerance test based on the IADPSG criteria, and management involved dietary or insulin interventions. We assessed outcomes such as hypertensive disorders (gestational hypertension, preeclampsia, and eclampsia), membrane rupture, preterm birth, small for gestational age (SGA), large for gestational age (LGA), and neonatal intensive care unit (NICU) admissions. Results Among 1003 twin pregnancies, 21.7% had GDM, with 11.5% receiving insulin. GDM was associated with older maternal age, higher BMI, and a family history of diabetes. Pregnant women with GDM had lower weekly weight gain (0.44 kg/week vs. 0.58 kg/week, p < 0.001) and experienced a higher risk of SGA neonates (aOR = 1.68, 95% CI: 1.06-2.67) and increased NICU admissions (aOR = 1.30, 95% CI: 1.00-1.69) compared to those without GDM. Additionally, dichorionic twins with GDM showed higher risks of SGA and NICU admissions, while monochorionic twins had no significant differences. A U-shaped relationship was identified between weekly weight gain and the rates of SGA and NICU admissions, with the lowest risk observed at a weekly weight gain of 0.75 kg for SGA and 0.57 kg for NICU admissions. Conclusions Applying singleton-derived IADPSG criteria to twin pregnancies may mitigate some maternal risks but elevates the risk for SGA neonates, suggesting a need for tailored diagnostic and management strategies for twin pregnancies. Trial registration Retrospectively registered.